Understanding the use of mobile ebooks among mathematics postgraduates - Letchumanan, Malathi (Walden University, 2024)
Objectives: The main objective of this study is to understand the factors that encourage the use of mobile ebooks among mathematics postgraduate students. Method: This study employed a qualitative case study approach. Eight mathematics postgraduate students from the algebra research group participated in the study. Data were collected via interview and analyzed by using constant comparative analysis. Results: Utilitarian, cognitive, affective, social norm, and content qualities were the main factors influencing the use of mobile ebooks among the participants. Conclusions: Mobile ebooks are easy to use and provide a meaningful platform to find information. In addition, the mobile ebook provides instant access to new information with a single finger click, thus enabling students to extract the needed information and make constructive comparisons on the subject matter. Theory and/or Practice Implications: Results expand understanding of the factors that motivate the use of mobile ebooks for learning activities among mathematics postgraduate students. In addition, the study also provides support for institutions planning to incorporate mobile ebooks as an important reference material for postgraduate learning and research activities.